Positive End-expiratory Pressure Alone Minimizes Atelectasis Formation in Nonabdominal Surgery: A Randomized Controlled Trial. (June 2018) - Östberg, Erland; Thorisson, Arnar; Enlund, Mats; Zetterström, Henrik; Hedenstierna, Göran; Edmark, Lennart
Abstract : Background: Various methods for protective ventilation are increasingly being recommended for patients undergoing general anesthesia. However, the importance of each individual component is still unclear. In particular, the perioperative use of positive end-expiratory pressure (PEEP) remains controversial. The authors tested the hypothesis that PEEP alone would be sufficient to limit atelectasis formation during nonabdominal surgery. Methods: This was a randomized controlled evaluator-blinded study. Twenty-four healthy patients undergoing general anesthesia were randomized to receive either mechanical ventilation with PEEP 7 or 9 cm H2 O depending on body mass index (n = 12) or zero PEEP (n = 12). No recruitment maneuvers were used. The primary outcome was atelectasis area as studied by computed tomography in a transverse scan near the diaphragm, at the end of surgery, before emergence. Oxygenation was evaluated by measuring blood gases and calculating the ratio of arterial oxygen partial pressure to inspired oxygen fraction (PaO2 /FIO2 ratio). Results: At the end of surgery, the median (range) atelectasis area, expressed as percentage of the total lung area, was 1.8 (0.3 to 9.9) in the PEEP group and 4.6 (1.0 to 10.2) in the zero PEEP group. The difference in medians was 2.8% (95% CI, 1.7 to 5.7%; P = 0.002). Oxygenation and carbon dioxide elimination were maintained in the PEEP group, but both deteriorated in the zero PEEP group. Conclusions: During nonabdominal surgery, adequate PEEP is sufficient to minimize atelectasis in healthy lungs and thereby maintain oxygenation. Thus, routine recruitment maneuvers seem unnecessary, and the authors suggest that they should only be utilized when clearly indicated. Visual Abstract: An online visual overview is available for this article athttp://links.lww.com/ALN/B728 . Abstract : Patients were randomly assigned to 7 to 9 cm H2 O or zero end-expiratory pressure. Atelectasis was assessed by computed tomography at the end of nonabdominal surgery while patients remained anesthetized. Positive end-expiratory pressure, without recruitment maneuvers, largely prevented atelectasis and maintained normal oxygenation.